6DOF knee kinematic alterations due to increased load levels - Yang, Tao; Huang, Yaxiang; Zhong, Guoqing; Kong, Lingchuang; Yan, Yuan; Lai, Huahao; Zeng, Xiaolong; Huang, Wenhan; Zhang, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Whether load carriage leads to six-degrees-of-freedom (6DOF) knee kinematic alterations remains unclear. Exploring this mechanism may reveal meaningful knee kinematic information that can be used to improve load carriage conditions, the design of protective devices, and the knowledge of the effects of load carriage on knees. We recruited 44 subjects to explore kinematic alterations from an unloaded state to 60% bodyweight (BW) load carriage. A three-dimensional gait analysis system was used to collect the knee kinematic data. One-way repeated analysis of variance (ANOVA) was used to explore the effects of load levels on knee kinematics. The effects of increasing load levels on knee kinematics were smooth with decreased or increased trends. We found that knees significantly exhibited increased lateral tibial translation (up to 1.2 mm), knee flexion angle (up to 1.4°), internal tibial rotation (up to 1.3°), and tibial proximal translation (up to 1.0 mm) when they went from an unloaded state to 60%BW load carriage during the stance phase (p < 0.05). Significant small knee adduction/abduction angle and posterior tibial translation alterations (<1°/mm) were also identified (p < 0.05). Load carriage can cause significant 6DOF knee kinematic alterations. The results showed that knee kinematic environments are challenging during increased load. Our results contain kinematic information that could be helpful for knee-protection-related activities, such as target muscle training to reduce abnormal knee kinematics and knee brace design.